PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 PADA JENJANG SEKOLAH DASAR\ - Shofa, Firsya Maurna; Hanik, Elya Umi (Fashluna: Jurnal Pendidikan Dasar dan Keguruan, 2020)
The COVID-19 pandemic has an impact on education in Indonesia. The learning process that was originally carried out at school has now changed to distance learning which is done from home. The use of information and communication technology provides convenience in learning during the COVID-19 Pandemic. This research was conducted to determine the benefits of information and communication technology in distance learning during the Covid-19 pandemic at the elementary school level. By using qualitative research methods literature study. The development of ICT in this globalization era it is growing very rapidly. The advancement of ICT brings convenience in the world of education, especially in distance learning where teachers and students can continue to carry out more efficient and meaningful learning through E-learning, WhatsApp, Zoom, YouTube, Classroom, and other applications. The Ministry of Education and Culture has provided a free learning platform called "Rumah Belajar" for areas where internet connections are not very good. Through this learning house the government collaborates with TVRI to deliver learning materials in the home study program. And in the distance learning process the learning process that students do is inseparable from the supervision of teachers and parents.